KEWENANGAN PEMERINTAH DAERAH KOTA PEKANBARU TERHADAP PELAKSANAAN PEMBINAAN PASAR SUKARAMAI TRADE CENTER: BERDASARKAN PASAL 34 AYAT (2) HURUF C PERATURAN DAERAH NOMOR 09 TAHUN 2014 TENTANG PENGELOLAAN PASAR RAKYAT, PUSAT PERBELANJAAN DAN TOKO SWALAYAN - Yuny Handayani Hrp; Dessy Artina; Ledy Diana (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Regional Goverments manage and manage their regions inthe hope of creating community welfare in their respective areas, one of which is the policy made by local goverments to improve the welfare of the people in the area, namely by Implementing Market Arrangement Authority in Pekanbaru City. The agency authorized and responsible for managing the people’s market is the market office. The Pekanbaru City Goverments, especially the Market Service, must be able and obliged and always strive for the People’s Market (including the Main Market and Supporting Market) to become an effective and profitable trading facility for the lower middle class community. For this reason, People’s Market should get support from the Pekanbaru City Goverments, both in the form of revitalization (market rejuvenation) and the daily management of the People’s Market in the form of structuring, empowering, fostering and monitoring that is carried out strictly. The purpose of writing this thesis, namely: First, to find out the implementation of the Regional Regulation Number 9 of 2014 conceming the Management of the People’s Market. Shopping Centers and Supermarkets in Pekanbaru City. Second. To find out the inhibiting factors that affect the Regional Government in the Pekanbaru Market Arrangement. This type of research is sociological legal research, where research wants to see the correlation between law and society, so as to be able to reveal the effectiveness of law enforcement in society and identify unwritten laws that apply to people in the field or to society. The data sources used were primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection techniques in this study were observation, interview, and literature review. After the data was collected, it was analyzed to draw conclusions. From the results of the study, it was concluded that, First, the implementation of Sukaramai Trade Center Market Development Based on Article 34 paragraph (2) letter C of Pekanbaru City Regional Regulation Number 9 of 2014 has not been carried out optimally by the government. Second, the inhibiting factors that influence the Regional Government in the Implementation of Pekanbaru Market Development are the legal factor itself, official staff factors, and unclear regulatory factors. Suggestions from the author, namely, the Pekanbaru City STC Market and Market Management Office pay more attention to the rights of traders in accordance with Regional Regulations Article 34 paragraph (2) letter C Number 9 of 2014